2021
DOI: 10.1080/02656736.2021.2000046
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of acoustic and thermal modeling in heterogeneous phantoms using the hybrid angular spectrum method

Abstract: Purpose: The aim was to quantitatively validate the hybrid angular spectrum (HAS) algorithm, a rapid wave propagation technique for heterogeneous media, with both pressure and temperature measurements. Methods: Heterogeneous tissue-mimicking phantoms were used to evaluate the accuracy of the HAS acoustic modeling algorithm in predicting pressure and thermal patterns. Acoustic properties of the phantom components were measured by a through-transmission technique while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We employed the hybrid angular spectrum (HAS) technique 19 to model ultrasound wave propagation. HAS extends the well‐known traditional angular spectrum method 20,21 to inhomogeneous models that more accurately represent complex tissue structures 19,22–24 . Vyas and Christensen found that HAS approximates the accuracy of the finite‐difference time‐domain technique with significantly shorter computation times 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed the hybrid angular spectrum (HAS) technique 19 to model ultrasound wave propagation. HAS extends the well‐known traditional angular spectrum method 20,21 to inhomogeneous models that more accurately represent complex tissue structures 19,22–24 . Vyas and Christensen found that HAS approximates the accuracy of the finite‐difference time‐domain technique with significantly shorter computation times 19 .…”
Section: Introductionmentioning
confidence: 99%
“…HAS extends the well-known traditional angular spectrum method 20,21 to inhomogeneous models that more accurately represent complex tissue structures. 19,[22][23][24] Vyas and Christensen found that HAS approximates the accuracy of the finitedifference time-domain technique with significantly shorter computation times. 19 Because HAS is more computationally efficient than most wave modeling strategies, it presents a promising alternative when performing iterative and computationally heavy optimization tasks.…”
mentioning
confidence: 99%
“…This is a significant problem and raises the concern that ongoing human studies using LOS may not be conclusive. Finitedifference time domain [13][14][15][16], hybrid angle spectrum [12,[17][18][19][20][21][22][23] or pseudo-spectral modeling [24][25][26] have been used for modeling of acoustic propagation through bone, however all those tools require individualized maps of the speed-of-sound and acoustic attenuation parameters as inputs. Those have traditionally been estimated using CT [27][28][29], but this can be difficult to justify as this increases radiation exposure and introduces cross-modality registration errors when using MRI for neuronavigation.…”
Section: Introductionmentioning
confidence: 99%